2017
DOI: 10.3389/fneur.2017.00687
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide and Levetiracetam Have No Effect on Sharp-Wave Ripple Rate

Abstract: Pathological high-frequency oscillations are a novel marker used to improve the delineation of epileptogenic tissue and, hence, the outcome of epilepsy surgery. Their practical clinical utilization is curtailed by the inability to discriminate them from physiological oscillations due to frequency overlap. Although it is well documented that pathological HFOs are suppressed by antiepileptic drugs (AEDs), the effect of AEDs on normal HFOs is not well known. In this experimental study, we have explored whether ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The effects of brivaracetam on ripple HFO and fast-ripple HFO remain to be clarified clinically and preclinically. The effects of levetiracetam on ripple HFO or sleep spindle remain to be clinically clarified; however, two preclinical studies revealed that levetiracetam predominantly inhibited fast-ripple HFO compared to ripple HFO [30,31]. These electrophysiological profiles of levetiracetam demonstrated by two preclinical physiological studies suggest that levetiracetam is a possible candidate antiseizure drug with reasonable pharmacological properties, predominantly suppressing fast-ripple HFO compared to ripple HFO.…”
Section: Candidate Mechanisms Of Adverse Behavioural Effects Of Briva...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of brivaracetam on ripple HFO and fast-ripple HFO remain to be clarified clinically and preclinically. The effects of levetiracetam on ripple HFO or sleep spindle remain to be clinically clarified; however, two preclinical studies revealed that levetiracetam predominantly inhibited fast-ripple HFO compared to ripple HFO [30,31]. These electrophysiological profiles of levetiracetam demonstrated by two preclinical physiological studies suggest that levetiracetam is a possible candidate antiseizure drug with reasonable pharmacological properties, predominantly suppressing fast-ripple HFO compared to ripple HFO.…”
Section: Candidate Mechanisms Of Adverse Behavioural Effects Of Briva...mentioning
confidence: 99%
“…Preclinical studies reported that levetiracetam suppressed the frequency of fast-ripple HFO, whereas the inhibitory effects of levetiracetam on the ripple HFO were weaker compared to fast-ripple HFO [30,31]. A recent systematic review reported that switching from levetiracetam to brivaracetam could improve adverse behavioural/psychiatric reactions induced by levetiracetam [32].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should determine whether IEDs and FRs are indeed pathologic versions of SWRs. Current antiepileptic drugs are not known to specifically affect the frequency of SWRs, but the ketogenic diet may be able to modulate pathologic oscillations . The restoration of SWRs to a physiologic state therefore represents an excellent target for the treatment of cognitive dysfunction, one of the most important comorbidities of epilepsy …”
Section: Clinical Relevancementioning
confidence: 99%
“…Particularly in humans, the ability to discriminate between normal HFOs and pathologic ones can be challenging because they display spectral overlap. Multiple studies tried to discriminate physiologic and pathologic HFOs according to their spectral and spatial features, relationship with sleep phases, background activity, phase relationship with slow waves, or their response to antiepileptic drugs …”
Section: In Vitro Activity With Relevance To Human Epilepsymentioning
confidence: 99%